Spremljanje dinamike vnosa in spiranja nitratnega dušika na porečju potoka Padež - Česnik, Katarina (Acta hydrotechnica, 2014)
The sensitivity of ecosystems to changes in the amounts of nitrogen in the environment is large. In order to protect them against overloads of nutrients and to allow their healthy development, the knowledge of the nitrogen mass balance is crucial. Differences in the amount of nitrogen occur because of increasing inputs from anthropogenic sources, but they are also due to meteorological, hydrological, geological and biological factors or, in other words, to biogeochemical circulation between the biotope and organisms. The data on stream water nitrate concentrations and nitrate concentrations in precipitation together with measurements of precipitations and Padež stream discharge were used to analyze nitrate-nitrogen input-output dynamics. The analysis is presented as a difference between inputs and outputs of nitrate-nitrogen per hectare of catchment area. The impact of seasonality could be observed. Watershed behaves as a sink or as a source of nitrate-nitrogen depending on the hydrological conditions and the amount of potentially available nitrate-nitrogen in soil which is flushed towards the stream and its concentrations in precipitation.
Keywords: biogeochemistry; biogeokemija; hidrološke razmere; hydrological conditions; nitrate nitrogen; nitratni dušik; Padež stream watershed; porečje Padeža